2003
DOI: 10.1038/nm876
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal vaccination decreases atherosclerotic lesion formation: molecular mimicry between Streptococcus pneumoniae and oxidized LDL

Abstract: During the progression of atherosclerosis, autoantibodies are induced to epitopes of oxidized low-density lipoprotein (oxLDL) and active immunization of hypercholesterolemic mice with oxLDL ameliorates atherogenesis. We unexpectedly found that many autoantibodies to oxLDL derived from 'naive' atherosclerotic mice share complete genetic and structural identity with antibodies from the classic anti-phosphorylcholine B-cell clone, T15, which protect against common infectious pathogens, including pneumococci. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
416
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 658 publications
(434 citation statements)
references
References 45 publications
8
416
1
3
Order By: Relevance
“…Our studies have revealed a most interesting and previously undescribed impact of T-bet deficiency, namely a Th2 shift in the T cell response to hypercholesterolemia, and a linked enhancement of serum titers of atheroprotective EO6͞T15 natural IgM antibodies (19,30). EO6͞T15 IgM autoantibodies may exert atheroprotective effects by inhibiting the uptake of Ox-LDL by macrophage scavenger receptors.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Our studies have revealed a most interesting and previously undescribed impact of T-bet deficiency, namely a Th2 shift in the T cell response to hypercholesterolemia, and a linked enhancement of serum titers of atheroprotective EO6͞T15 natural IgM antibodies (19,30). EO6͞T15 IgM autoantibodies may exert atheroprotective effects by inhibiting the uptake of Ox-LDL by macrophage scavenger receptors.…”
Section: Resultsmentioning
confidence: 84%
“…In turn, it was shown that the IL-5 provided noncognate help to B-1 cells and expansion of EO6-secreting cells (19). Because we have recently shown that a near monoclonal expansion of EO6͞T15 antibodies in vivo, produced by immunization of mice with heat-killed Streptococcus pneumoniae, decreased the extent of atherosclerosis (30), the enhanced titer of EO6͞T15 we observed in the T-bet-deficient mice may well contribute in part to the atheroprotective effect observed with T-bet deficiency. Indeed, the enhanced IgM anti-Ox-LDL antibody titer observed in the T-bet-deficient mice may contain other such atheroprotective subsets of natural antibodies as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of IgM and IgG‐α‐oxLDL antibodies were measured as described previously 40, 43. In short, serum samples were diluted 500 times for IgM and 2000 times for IgG‐α‐oxLDL antibody measurements.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, anti‐oxLDL autoantibodies have also been associated with lower oxLDL levels38 and decreased carotid atherosclerosis as well 39. In addition, vaccination with a pneumococcal vaccine, mimicking oxLDL epitopes, was shown to attenuate atherosclerotic lesion formation in mice40 and, according to a recent meta‐analysis, also prevents CVD in adults 41…”
Section: Introductionmentioning
confidence: 99%